Measuring the importance of the uniform nonsynchronization hypothesis - Daniel Dias; Carlos Robalo Marques; Jo\~ao M. C. Santos Silva (European Central Bank (ECB), 2006)
In this paper we critically reappraise some measures of the importance of time-dependent price setting rules and propose an alternative way to gauge the significance of this type of price setting behaviour. The merits of the proposed measure are highlighted in an application using micro-data. Our results suggest that a large proportion of price trajectories may be compatible with simple time-dependent price setting mechanisms but the strength of this evidence very much depends on the way that is used to evaluate the importance of this type of behaviour.
Keywords: D40; E31; L11; 330; perfect synchronization; Time-dependent price setting models; uniform staggering; Marktmechanismus; Theorie